Predicting students’ aggressive behavior by coping mechanisms and interpersonal communication - Eva Yulina; Asih Menanti; Suryani Hardjo (Institut Agama Islam Negeri Langsa, 2021)
This study aims to find out the relationship between coping mechanisms and interpersonal communication with aggressive behavior of students of Department of Automotive at SMK PAB 12 Saentis. This type of research is quantitative by involving 93 students as a sample taken with total sampling techniques with the first screening of aggressive behavior tendencies. This study used 3 (three) coping mechanism scales, interpersonal communication scales, and aggressive behavior scales to obtain data analyzed using multiple regression analysis. The results showed a negative relationship between coping mechanisms and interpersonal communication with students’ aggressive behavior simultaneously and partially. Coping mechanisms and interpersonal communication can predict the emergence of aggressive behavior of students by 52.8%.